SCM-33 molecular sieve, its preparation method and its use

JP7641296B2Active Publication Date: 2025-03-06CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2022568572
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-05-11
Filing Date
2020-10-28
Publication Date
2025-03-06
Estimated Expiration
2040-10-28

Smart Images

  • Figure 0007641296000020
    Figure 0007641296000020
  • Figure 0007641296000021
    Figure 0007641296000021
  • Figure 0007641296000022
    Figure 0007641296000022
Patent Text Reader

Abstract

The present invention discloses SCM-33 molecular sieve, its preparation method and its use. SCM-33 molecular sieve has the formula "SiO2·1 / xXO 1.5 MMO 0.5 " (wherein X is a framework trivalent element, the molar ratio of Si / X is x≧5, M is a framework balance cation, and the molar ratio of M / Si is 0
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the field of molecular sieves, in particular to SCM-33 molecular sieve, its preparation method and its uses. [Background technology]

[0002] Zeolites, or so-called molecular sieves, are a kind of porous crystalline materials, with regular molecular size, pore structure, relatively strong acidity, and high hydrothermal stability. They are widely used in catalysis, adsorption, ion exchange, and other fields, and play an irreplaceable role. At present, there are 248 molecular sieve topologies recognized by the International Zeolite Association.

[0003] In 1995, Marler et al. first reported the synthesis of the pure silicon molecular sieve RUB-3 and elucidated its structure (Zeolites, 1995, No. 15, pp. 388-399), and this molecular sieve was subsequently given the framework type code RTE by the International Zeolite Association. Molecular sieves with the RTE structure are generally referred to as rte ([4 4 5 4 6 2 ]) units and [4 6 5 4 6 6 8 2 ] cage structure, and the interconnected cages form a one-dimensional pore structure with eight-membered ring openings (Microporous and Mesoporous Materials, 1998, No. 26, pp.49-59). The RTE molecular sieve has a pore diameter of 3.6 x 4.3 Å, which is equivalent to the diameter of many small gas molecules, allowing for greater applicability of the molecular sieve for gas adsorption and separation; meanwhile, the unique pore cage structure also gives the RTE molecular sieve the potential for application in the field of catalysis.

[0004] RUB-3 is currently the only molecular sieve with an RTE topology, but it faces the following problems in its synthesis: 1) The exo-2-aminobicyclo[2.2.1]heptane of the organic template is expensive, and as a result of being used in large quantities, the cost of molecular sieve synthesis becomes high; 2) The crystal growth rate is low, and the synthesis period is more than 90 days, even up to one year; 3) The crystals are columnar with a size of 50×50×150 μm, which is too large; 4) The framework is a silicon-based framework, and it is difficult to introduce catalytic active centers.

[0005] Therefore, developing a new molecular sieve with an RTE topology and its preparation method has very practical significance.

Summary of the Invention

[0006] The present invention provides an SCM-33 molecular sieve, its preparation method and its usage. The SCM-33 molecular sieve is a new molecular sieve with an RTE topology. The molecular sieve requires a short preparation time, has a low synthesis cost, has a smaller crystal size, and can introduce elements other than Si as catalytic active centers into its framework.

[0007] According to a first aspect of the present invention, an SCM-33 molecular sieve is provided. The SCM-33 molecular sieve has a schematic chemical composition as shown in the formula "SiO2·1 / xXO 1.5 ·mMO 0.5 " (wherein x is a framework trivalent element, the molar ratio of Si / X is x≥5, M is a framework balancing cation, and the molar ratio of M / Si is 0<m≤1). The SCM-33 molecular sieve has an X-ray diffraction pattern as shown in the following table:

[0008]

Table 1

[0009] Furthermore, the X-ray diffraction pattern of the SCM-33 molecular sieve has the X-ray diffraction peaks as shown in the following table:

[0010] [Table 2]

[0011] Additionally, the X-ray diffraction pattern of the SCM-33 molecular sieve also includes the X-ray diffraction peaks shown in the table below:

[0012] [Table 3]

[0013] In addition, the X-ray diffraction pattern of the SCM-33 molecular sieve further includes the X-ray diffraction peaks shown in the table below:

[0014] [Table 4]

[0015] Furthermore, in the schematic chemical composition formula of the SCM-33 molecular sieve, the molar ratio of Si / X is preferably 10≦x≦200, more preferably 15≦x≦150, even more preferably 20≦x≦120, and / or the molar ratio of M / Si is preferably 0.01≦m≦0.85, more preferably 0.015≦m≦0.8, even more preferably 0.02≦m≦0.75.

[0016] The synthesis method of SCM-33 molecular sieve is based on the formula "qQ SiO2 1 / xXO 1.5 mmO 0.5·zH2O」(wherein the Si / X molar ratio is x ≧ 5, preferably 10 ≦ x ≦ 200, more preferably 15 ≦ x ≦ 150, still more preferably 20 ≦ x ≦ 120), including the as-manufactured form, where the M / Si molar ratio is 0 < m ≦ 1, preferably 0.01 ≦ m ≦ 0.85, more preferably 0.015 ≦ m ≦ 0.8, still more preferably 0.02 ≦ m ≦ 0.75; the H2O / Si molar ratio is 0.005 ≦ z ≦ 2, preferably 0.01 ≦ z ≦ 1.5, more preferably 0.01 ≦ z ≦ 1, still more preferably 0.02 ≦ z ≦ 0.5; Q is an organic template, and the Q / Si molar ratio is 0.01 ≦ q ≦ 1.0, preferably 0.02 ≦ q ≦ 0.5, more preferably 0.05 ≦ q ≦ 0.5, still more preferably 0.05 ≦ q ≦ 0.3).

[0017] The organic template Q is preferably selected from substances containing an isopropyltrimethylammonium cation having the following structural formula:

[0018] [Chemical formula]

[0019] Furthermore, the organic template Q is more preferably a hydroxide containing an isopropyltrimethylammonium cation, for example, isopropyltrimethylammonium hydroxide.

[0020] Furthermore, the framework trivalent element X is selected from at least one of aluminum, boron, iron, gallium, indium and chromium. Furthermore, the framework balance cations M are selected from at least one of protons, ammonium cations, sodium cations, potassium cations, lithium cations, rubidium cations, cesium cations, magnesium cations, calcium cations, strontium cations and barium cations, preferably M comprises at least potassium cations or M comprises at least potassium cations and sodium cations. When comprising potassium cations and sodium cations, M preferably comprises more potassium cations than sodium cations.

[0021] Additionally, up to 10 wt. % of the Si atoms in the SCM-33 molecular sieve are replaced with at least one non-silicon tetravalent framework element Y, preferably selected from at least one of germanium, tin, titanium, zirconium and hafnium.

[0022] Furthermore, the average crystal grain size of the SCM-33 molecular sieve is about 100-200 nm.

[0023] According to a second aspect of the present invention, there is provided a method for preparing the aforementioned SCM-33 molecular sieve, comprising mixing a silicon source, a framework trivalent element X source, a framework balance cation M source, an organic template Q, and water for crystallization reaction to obtain the SCM-33 molecular sieve.

[0024] In addition, the method for preparing the SCM-33 molecular sieve may also include mixing a source of non-silicon tetravalent framework element Y, a silicon source, a source of framework trivalent element X, a source of framework balance cation M, an organic template Q and water for crystallization reaction to obtain the SCM-33 molecular sieve.

[0025] Furthermore, the organic template Q is selected from substances containing an isopropyltrimethylammonium cation, the structural formula of which is as follows:

[0026] [ka]

[0027] Furthermore, the organic template Q is preferably a hydroxide containing an isopropyltrimethylammonium cation, such as isopropyltrimethylammonium hydroxide.

[0028] Further, the silicon source is selected from at least one of water glass, silica sol, solid silica gel, particulate silica, amorphous silica, diatomaceous earth, zeolite molecular sieves, and tetraalkoxysilanes.

[0029] Furthermore, the source of the framework trivalent element X is selected from at least one of an aluminum source, a boron source, an iron source, a gallium source, an indium source, and a chromium source; the aluminum source is preferably selected from at least one of aluminum sulfate, sodium aluminate, aluminum nitrate, aluminum chloride, pseudoboehmite, aluminum oxide, aluminum hydroxide, aluminosilicate zeolite, aluminum carbonate, aluminum, aluminum isopropoxide, and aluminum acetate; the boron source is preferably selected from sodium borate, sodium tetraborate, amorphous borate, sodium tetrabo ... The iron source is preferably selected from at least one of iron(III) sulfate, iron(III) nitrate, ferric halide (e.g., iron(III) chloride), ferrocene, and iron(III) citrate; the gallium source, indium source, and chromium source may be selected from at least one of conventional materials in the art, such as gallium oxide, gallium nitrate, indium oxide, indium nitrate, chromium chloride, and chromium nitrate.

[0030] Further, the source of framework balance cations M is selected from at least one of a proton source, an ammonium cation source, a sodium potassium cation source, a lithium cation source, a rubidium cation source, a cesium cation source, a magnesium cation source, a calcium cation source, a strontium cation source, and a barium cation source, preferably the M source comprises at least a potassium cation source, or the M source comprises at least a potassium cation source and a sodium cation source. When a potassium cation source and a sodium cation source are used, it is preferable to use more potassium cations than sodium cations, for example, the molar ratio of potassium / sodium is 1.1 or more. The potassium cation source is preferably selected from at least one of potassium oxide, potassium hydroxide, potassium carbonate, potassium bicarbonate, potassium chloride, potassium nitrate, potassium sulfate, and potassium fluoride; the sodium cation source is preferably selected from at least one of sodium oxide, sodium hydroxide, sodium carbonate, sodium bicarbonate, sodium chloride, sodium nitrate, sodium sulfate, and sodium fluoride.

[0031] Furthermore, the source of the non-silicon tetravalent framework element Y is preferably selected from at least one of a germanium source, a tin source, a titanium source, a zirconium source, and a hafnium source, and more preferably selected from at least one of a germanium oxide source, a tin oxide source, a titanium oxide source, a zirconium oxide source, and a hafnium oxide source.

[0032] Furthermore, the molar ratio of the organic template Q, silicon source (based on SiO2), X source (based on X2O3), M source (based on M2O or MO), and water is Q:SiO2:X2O3:M2O (or MO):H2O=0.05-1:0.1:0-0.1:0-0.5:10-100, where the amount of the X source and M source is not 0, preferably Q:SiO2:X2O3:M2O (or MO):H2O=0.15-0.55:1:0.0042-0.033:0.01-0.375:14-55.

[0033] Furthermore, the molar ratio of the non-silicon tetravalent framework element Y source (based on the corresponding oxide YO2) to the silicon source (based on SiO2) is YO2 / SiO2=0 to 0.1, preferably 0.01 to 0.1, more preferably 0.01 to 0.08.

[0034] Further, the conditions of the crystallization reaction include the following: crystallization at 100-200°C for 30-400 hours, preferably crystallization at 110-190°C for 48-300 hours, and more preferably crystallization at 120-180°C for 72-200 hours.

[0035] After the crystallization reaction, conventional post-treatments such as filtration, washing, drying, etc. are carried out to prepare an as-prepared powder of the molecular sieve, and then the as-prepared powder is calcined to obtain the molecular sieve.

[0036] According to a third aspect of the present invention there is provided a molecular sieve composite comprising an SCM-33 molecular sieve according to the first aspect described above, or prepared according to the method of the second aspect described above, and a binder.

[0037] According to a fourth aspect of the present invention there is provided the use of an SCM-33 molecular sieve according to the first aspect described above, an SCM-33 molecular sieve according to the second aspect described above, or an SCM-33 molecular sieve composite according to the third aspect described above, as an adsorbent or catalyst.

[0038] The SCM-33 molecular sieve of the present invention is a novel non-pure silicon molecular sieve whose framework topology is RTE and different from RUB-3, enriching the RTE molecular sieve type.

[0039] The SCM-33 molecular sieve of the present invention has standard molecular diameter, pore structure, strong acidity, ion exchange performance, and high thermal and hydrothermal stability. The crystal size of the obtained SCM-33 zeolite molecular sieve is about 100-200 nm, which avoids the restricted mass transfer and diffusion in the pores caused by bulky crystals.

[0040] The preparation method of SCM-33 molecular sieve provided by the present invention utilizes low-cost organic template, which saves synthesis cost compared with the prior art; the molecular sieve needs a short crystallization time, which greatly shortens the synthesis time; the present method allows various elements such as Al, Ti, Zr and Fe to be introduced into the framework to generate various catalytic active centers, which can meet the needs of various catalytic reactions and have wider applications. The method of the present invention is simple to operate, highly efficient, and beneficial to industrial popularization. [Brief description of the drawings]

[0041] [Figure 1] 1 is an X-ray diffraction pattern of the sample obtained in Example 1 before firing. [Diagram 2] 1 shows an X-ray diffraction pattern of the sample obtained in Example 1 after firing. [Diagram 3] 1 is a scanning electron microscope (SEM) photograph of a sample obtained in Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0042] In order to facilitate the understanding of the present invention, the following examples are listed in the present invention. However, those skilled in the art should understand that these examples are only useful for helping to understand the present invention, and should not be considered as specific limitations on the present invention.

[0043] In the context of this specification, in the X-ray diffraction data of molecular sieves, vw, w, m, s, vs indicate the intensity of the diffraction peaks, where vw refers to very weak, w refers to weak, m refers to medium, s refers to strong, and vs refers to very strong, which are well known to those skilled in the art. Generally, vw is less than 5; w is 5-20; m is 20-40; s is 40-70; vs is greater than 70.

[0044] In the context of this specification, the structure of the molecular sieve is confirmed by the X-ray diffraction (XRD) pattern, which is determined by an X-ray powder diffractometer equipped with a Cu-Kα source and a Ni filter, where the Kα1 wavelength is λ=1.5405980 Å.

[0045] In the present invention, an X'Pert PRO X-ray powder diffractometer (XRD) manufactured by PANalytical BV is used, with a working voltage of 40 kV, a current of 40 mA, and a scanning range of 5 to 40°. The morphology of the product is measured by a HITACHI S-4800 field emission scanning electron microscope (Fe-SEM).

[0046] In particular, it should be noted that two or more aspects (or embodiments) disclosed in the context of this specification can be arbitrarily combined with each other, and the technical solutions (such as methods or systems) so formed are part of the original disclosure in this specification and are also included in the scope of protection in this specification.

[0047] Unless otherwise indicated, all percentages, parts, ratios, etc. described herein are by weight, except where taking a weight basis is in accordance with the conventional understanding of those skilled in the art.

[0048] [Example 1] 2.5g of sodium metaaluminate (Al2O3 41wt%, Na2O 58wt%) and 17.5g of potassium hydroxide solution (30wt%) were dissolved in 28g of water, 39.4g of isopropyltrimethylammonium hydroxide solution (20wt%) was added and stirred uniformly, and finally 60g of Ludox AS-40 silica sol was slowly added with stirring; after stirring for 1 hour, the above mixture was charged into a polytetrafluoroethylene lined crystallization kettle and placed in an oven at 155°C for crystallization for 144 hours. After reaction, the solid was filtered, washed with distilled water and dried at 100°C to obtain the as-prepared powder of SCM-33 molecular sieve. The XRD pattern is shown in Figure 1. The as-prepared powder solid was placed into a muffle furnace and calcined at 550°C for 5 hours to obtain the final product. The XRD pattern is shown in Figure 2 and the SEM photo of SCM-33 molecular sieve is shown in Figure 3.

[0049] Here, the XRD pattern data of the final product obtained in Example 1 is shown in Table 1:

[0050] [Table 5]

[0051] [Example 2] 2.5g of sodium metaaluminate (Al2O3 41wt%, Na2O 58wt%) and 13.7g of potassium hydroxide solution (30wt%) were dissolved in 64g of water, 39.4g of isopropyltrimethylammonium hydroxide solution (20wt%) was added and stirred uniformly, and finally 60g of Ludox AS-40 silica sol was slowly added with stirring; after stirring for 1 hour, the above mixture was put into a polytetrafluoroethylene-lined crystallization kettle and placed in an oven at 160°C for crystallization for 120 hours. After the reaction, the solid was filtered, washed, dried and calcined (post-treatment conditions were the same as in Example 1) to obtain SCM-33 zeolite molecular sieve. The XRD pattern was the same as in Figure 2, and the XRD pattern data of the final product obtained in Example 2 is shown in Table 2:

[0052] [Table 6]

[0053] [Example 3] 7.5g sodium hydroxide solution (30wt%), 15g potassium hydroxide solution (30wt%), 40g H2O and 47.3g isopropyltrimethylammonium hydroxide solution (20wt%) were uniformly stirred, and 45g Ludox AS-40 silica sol was slowly added with stirring; after stirring for 1 hour, 6.6g USY molecular sieve (SiO2 / Al2O3=12) was added; after stirring for 1.5 hours, the above mixture was put into a polytetrafluoroethylene lined crystallization kettle and placed in an oven at 165°C for crystallization for 96 hours. After reaction, the solid was filtered, washed, dried and calcined (post-treatment reaction conditions were the same as in Example 1), to obtain SCM-33 zeolite molecular sieve, and the XRD pattern is the same as in Figure 2. Here, the XRD pattern data of the final product obtained in Example 3 is shown in Table 3:

[0054] [Table 7]

[0055] [Example 4] 4.2g of aluminum sulfate octadecahydrate, 6.2g (30% by weight) of sodium hydroxide solution and 13.7g (30% by weight) of potassium hydroxide solution were dissolved in 21.1g of water, 110g (20% by weight) of isopropyltrimethylammonium hydroxide solution was added and stirred uniformly, and finally 54g of Ludox AS-40 silica gel was slowly added with stirring; after stirring for 1 hour, the mixture was put into a polytetrafluoroethylene-lined crystallization kettle and placed in an oven at 150°C for 180 hours to crystallize. After the reaction, the solid was filtered, washed, dried and calcined (post-treatment reaction conditions were the same as in Example 1), and the SCM-33 zeolite molecular sieve was obtained, and the X-ray diffraction pattern is the same as in Figure 2.

[0056] [Example 5] 2g of aluminum isopropoxide was added to 40g of isopropyltrimethylammonium hydroxide solution (20wt%) and 12g of potassium hydroxide solution (30wt%); after dissolution, 75g of water was added, and 52g of tetraethyl orthosilicate was slowly added; after complete hydrolysis, the above mixture was put into a polytetrafluoroethylene-lined crystallization kettle and placed in an oven at 175°C for crystallization for 144 hours. After reaction, the solid was filtered, washed, dried and calcined (post-treatment reaction was the same as in Example 1) to obtain SCM-33 zeolite molecular sieve, whose X-ray diffraction pattern is the same as in Figure 2.

[0057] [Example 6] 9.7g of rubidium chloride and 26g of potassium hydroxide solution (30wt%) were dissolved in 68.5g of water, 39.4g of isopropyltrimethylammonium hydroxide solution (20wt%) was added and stirred uniformly, and 54.6g of Ludox AS-40 silica sol was slowly added with stirring; after stirring for 1 hour, 5g of USY molecular sieve (SiO2 / Al2O3=12) was added; after stirring for 1.5 hours, the above mixture was put into a polytetrafluoroethylene-lined crystallization kettle and placed in an oven at 145°C for crystallization for 192 hours. After reaction, the solid was filtered, washed, dried and calcined (post-treatment reaction conditions were the same as in Example 1) to obtain SCM-33 zeolite molecular sieve, whose X-ray diffraction pattern is the same as in Figure 2.

[0058] [Example 7] 0.6g of pseudoboehmite (Al2O3 70% by weight) and 17g of potassium hydroxide solution (30% by weight) were dissolved in 30g of water, 49.3g of isopropyltrimethylammonium hydroxide solution (20% by weight) was added and stirred uniformly, and 15g of water glass (SiO2 27% by weight, Na2O 8.4% by weight) and 45g of Ludox AS-40 silica sol were slowly added with stirring; after stirring for 1 hour, the above mixture was put into a polytetrafluoroethylene-lined crystallization kettle and placed in an oven at 160°C for crystallization for 168 hours. After the reaction, the solid was filtered, washed, dried and calcined (post-treatment reaction conditions were the same as in Example 1) to obtain SCM-33 zeolite molecular sieve, whose X-ray diffraction pattern is the same as in Figure 2.

[0059] [Example 8] 1.3g of boric acid, 9g of sodium hydroxide solution (30wt%) and 14g of potassium hydroxide solution (30wt%) were dissolved in 41g of water, 49.3g of isopropyltrimethylammonium hydroxide solution (20wt%) was added and stirred uniformly, and 75g of Ludox AS-40 silica sol was slowly added under stirring; after stirring for 1 hour, the above mixture was put into a polytetrafluoroethylene-lined crystallization kettle and placed in an oven at 160°C for crystallization for 192 hours. After reaction, the solid was filtered, washed, dried and calcined (post-treatment reaction conditions were the same as in Example 1), and SCM-33 zeolite molecular sieve was obtained, and the XRD pattern is the same as in Figure 2. Here, the XRD pattern data of the final product obtained in Example 8 is shown in Table 4:

[0060] [Table 8]

[0061] [Example 9] 4.8g of ferric nitrate nonhydrate, 9g of sodium hydroxide solution (30% by weight), and 14g of potassium hydroxide solution (30% by weight) were dissolved in 150g of water, 49.3g of isopropyltrimethylammonium hydroxide solution (20% by weight) was added and stirred uniformly, and 75g of Ludox AS-40 silica sol was slowly added with stirring; after stirring for 1 hour, the mixture was put into a polytetrafluoroethylene-lined crystallization kettle and placed in an oven at 150°C for crystallization for 216 hours. After the reaction, the solid was filtered, washed, dried, and calcined (post-treatment reaction conditions were the same as in Example 1), and the SCM-33 zeolite molecular sieve was obtained, and the X-ray diffraction pattern was the same as in Figure 2.

[0062] [Example 10] 4g titanium sulfate, 0.4g boric acid, 8g sodium hydroxide solution (30wt%), 15g potassium hydroxide solution (30wt%) were dissolved in 50g water, 49.3g isopropyltrimethylammonium hydroxide solution (20wt%) was added and stirred uniformly, and 60g Ludox AS-40 silica sol was slowly added under stirring; after stirring for 1 hour, the above mixture was placed in a polytetrafluoroethylene lined crystallization kettle and placed in an oven at 170°C for crystallization for 120 hours. After reaction, the solid was filtered, washed, dried and calcined (post-treatment reaction conditions were the same as in Example 1), and SCM-33 zeolite molecular sieve was obtained, and the XRD pattern is the same as in Figure 2. Here, the XRD pattern data of the final product obtained in Example 10 is shown in Table 5:

[0063] [Table 9]

[0064] [Comparative Example 1] 2.5g sodium metaaluminate (Al2O3 41wt%, Na2O 58wt%), 17.5g potassium hydroxide solution (30wt%) were dissolved in 28g water, 30g tetramethylammonium hydroxide solution (20wt%) was added and stirred evenly, and finally 60g Ludox AS-40 silica sol was slowly added with stirring; after stirring for 1 hour, the above mixture was put into a polytetrafluoroethylene lined crystallization kettle and placed in an oven at 155°C for crystallization for 144 hours. After reaction, the solid was filtered, washed, dried and calcined (post-treatment reaction conditions are the same as in Example 1) to obtain a molecular sieve, which is the RUT molecular sieve after X-ray diffraction analysis. Its XRD pattern is obviously different from that in Figure 2. The XRD pattern data is shown in Table 6:

[0065] [Table 10]

[0066] [Comparative Example 2] 2.5g sodium metaaluminate (Al2O3 41wt%, Na2O 58wt%), 17.5g potassium hydroxide solution (30wt%) were dissolved in 28g water, 48.7g tetraethylammonium hydroxide solution (20wt%) was added and stirred evenly, and finally 60g Ludox AS-40 silica sol was slowly added with stirring; after stirring for 1 hour, the above mixture was put into a polytetrafluoroethylene lined crystallization kettle and placed in an oven at 155°C for crystallization for 144 hours. After reaction, the solid was filtered, washed, dried and calcined (post-treatment reaction conditions were the same as in Example 1) to obtain a molecular sieve, which was found to be a BEA molecular sieve after X-ray diffraction analysis. Its XRD pattern is obviously different from that in Figure 2. The XRD pattern data is shown in Table 7:

[0067] [Table 11]

Claims

1. The formula “SiO 2 1 / xXO 1.5 ・mMO 0.5 (wherein X is a framework trivalent element, the molar ratio of Si / X is ≧5, and M is a framework balance cation, the molar ratio of M / Si is 0<m≦1), and has an X-ray diffraction pattern as shown in the table below. 【Table 1】

2. 2. The molecular sieve of claim 1, wherein the X-ray diffraction pattern of the SCM-33 molecular sieve has the X-ray diffraction peaks shown in the table below. 【Table 2】

3. 3. The molecular sieve of claim 2, wherein the X-ray diffraction pattern of the SCM-33 molecular sieve also includes the X-ray diffraction peaks shown in the table below. 【Table 3】

4. 4. The molecular sieve of claim 3, wherein the X-ray diffraction pattern of the SCM-33 molecular sieve also includes the X-ray diffraction peaks shown in the table below. 【Table 4】

5. 5. The molecular sieve according to claim 1, wherein the molar ratio of Si / X is 10≦x≦200, preferably 15≦x≦150, more preferably 20≦x≦120, and / or the molar ratio of M / Si is 0.01≦m≦0.85, preferably 0.015≦m≦0.8, more preferably 0.02≦m≦0.

75.

6. The as-produced morphology of the SCM-33 molecular sieve is represented by the formula "qQ.SiO 2 1 / xXO 1.5 ・mMO 0.5 ・zH 2 1, wherein the molar ratio x of Si / X is ≧5, preferably 10≦x≦200, more preferably 15≦x≦150, and even more preferably 20≦x≦120; the molar ratio of M / Si is 0<m≦1, preferably 0.01≦m≦0.85, more preferably 0.015≦m≦0.8, and even more preferably 0.02≦m≦0.75; 2 6. The molecular sieve according to claim 1, wherein the molar ratio of O / Si is 0.005≦z≦2, preferably 0.01≦z≦1.5, more preferably 0.015≦z≦1, and even more preferably 0.02≦z≦0.5; Q is an organic template; and the molar ratio of Q / Si is 0.01≦q≦1.0, preferably 0.02≦q≦0.5, more preferably 0.05≦q≦0.5, and even more preferably 0.05≦q≦0.

3.

7. 7. The molecular sieve of claim 1, wherein the framework trivalent element X is selected from at least one of aluminum, boron, iron, gallium, indium and chromium, and the framework balance cations M are selected from at least one of protons, ammonium cations, sodium cations, potassium cations, lithium cations, rubidium cations, cesium cations, magnesium cations, calcium cations, strontium cations and barium cations, preferably M comprises at least potassium cations and sodium cations, and when M comprises potassium cations and sodium cations, preferably it comprises more potassium cations than sodium cations.

8. Q is an organic template, preferably selected from materials containing isopropyltrimethylammonium cations, the structural formula of which is as follows: 【Chemistry 1】 7. The molecular sieve according to claim 6, characterized in that it is a hydroxide containing an isopropyltrimethylammonium cation, for example isopropyltrimethylammonium hydroxide.

9. 9. The molecular sieve according to any one of claims 1 to 8, characterized in that up to 10 wt.% of Si atoms in the SCM-33 molecular sieve are replaced by at least one non-silicon tetravalent framework element Y, preferably selected from at least one of germanium, tin, titanium, zirconium and hafnium.

10. 9. A method for producing the molecular sieve of claim 1, comprising mixing a silicon source, a framework trivalent element X source, a framework balance cation M source, an organic template Q, and water for crystallization reaction to obtain SCM-33 molecular sieve.

11. 10. The method for producing the molecular sieve of claim 9, comprising mixing a source of non-silicon tetravalent framework element Y, a silicon source, a source of framework trivalent element X, a source of framework balance cation M, an organic template Q, and water for crystallization reaction to obtain SCM-33 molecular sieve.

12. The organic template Q is SiO 2 The silicon source based on X 2 O 3 The X source based on M 2 The M source based on O or MO, and water have a molar ratio of Q:SiO 2 :X 2 O 3 : M 2 O or MO:H 2 O=0.05-1:1:0-0.1:0-0.5:10-100, where the amount of X source and M source is not 0, and preferably Q:SiO 2 :X 2 O 3 : M 2 O:H 2 The method according to claim 10 or 11, characterized in that O=0.15-0.55:1:0.0042-0.033:0.01-0.375:14-55.

13. The corresponding oxide YO 2 The non-silicon tetravalent framework element Y source based on SiO 2 The molar ratio of the silicon source based on 2 / SiO 2 The method according to claim 11, characterized in that is greater than 0 to 0.1, preferably 0.01 to 0.1, more preferably 0.01 to 0.

08.

14. 14. The method according to any one of claims 10 to 13, characterized in that the crystallization conditions comprise crystallization at 100-200°C for 30-400 hours, preferably at 110-190°C for 48-300 hours, more preferably at 120-180°C for 72-200 hours.

15. The organic template Q is selected from those including an isopropyltrimethylammonium cation, the structural formula of which is as follows: 【Chemistry 2】 The organic template Q is preferably a hydroxide containing an isopropyltrimethylammonium cation, such as isopropyltrimethylammonium hydroxide; The silicon source is selected from at least one of water glass, silica sol, solid silica gel, particulate silica, amorphous silica, diatomaceous earth, zeolite molecular sieve, and tetraalkoxysilane; The source of the framework trivalent element X is selected from at least one of an aluminum source, a boron source, an iron source, a gallium source, an indium source, and a chromium source; the aluminum source is preferably selected from at least one of aluminum sulfate, sodium aluminate, aluminum nitrate, aluminum chloride, pseudoboehmite, aluminum oxide, aluminum hydroxide, aluminosilicate molecular sieves, aluminum carbonate, aluminum, aluminum isopropoxide, and aluminum acetate; the boron source is preferably boric acid, sodium tetraborate, , amorphous boron oxide, potassium borate, sodium metaborate, ammonium tetraborate, and organic boron esters; the iron source is preferably selected from at least one of ferric sulfate, ferric nitrate, ferric halides (e.g., ferric chloride), ferrocene, and ferric citrate; the gallium source, indium source, and chromium source may be selected from at least one of gallium oxide, gallium nitrate, indium oxide, indium nitrate, chromium chloride, and chromium nitrate; said source of framework balance cations M is selected from at least one of a proton source, an ammonium cation source, a sodium cation source, a potassium cation source, a lithium cation source, a rubidium cation source, a caesium cation source, a magnesium cation source, a calcium cation source, a strontium cation source, and a barium cation source, preferably said M source comprises at least a potassium cation source or said M source comprises at least a potassium cation source and a sodium cation source; when said potassium cation source and said sodium cation source are used, it is preferred to use more potassium cations than sodium cations, e.g. the potassium / sodium molar ratio is 1.1 or more, wherein said potassium cation source is preferably selected from at least one of potassium oxide, potassium hydroxide, potassium carbonate, potassium bicarbonate, potassium chloride, potassium nitrate, potassium sulfate, and potassium fluoride; said sodium cation source is preferably selected from at least one of sodium oxide, sodium hydroxide, sodium carbonate, sodium bicarbonate, sodium chloride, sodium nitrate, sodium sulfate, and sodium fluoride; and / or The non-silicon tetravalent framework element Y source is preferably selected from at least one of a germanium source, a tin source, a titanium source, a zirconium source and a hafnium source, more preferably selected from at least one of a germanium oxide source, a tin oxide source, a titanium oxide source, a zirconium oxide source and a hafnium oxide source; Use according to any one of claims 10 to 14, characterized in that

16. A molecular sieve composite comprising the SCM-33 molecular sieve of any one of claims 1 to 9 and a binder.

17. Use of the SCM-33 molecular sieve according to any one of claims 1 to 9, the SCM-33 molecular sieve prepared by the method according to any one of claims 10 to 15, or the composite according to claim 16 as an adsorbent or catalyst.

Citation Information

Patent Citations

  • UZM-37 Aluminosilicate Zeolite

    JP2013523583A

  • Synthesis of *MRE framework type molecular sieves

    US20190276323A1

  • Processes using UZM-37 aluminosilicate zeolite

    US7982084B1